2022
DOI: 10.1016/j.epsl.2021.117332
|View full text |Cite
|
Sign up to set email alerts
|

Downward-propagating eruption following vent unloading implies no direct magmatic trigger for the 2018 lateral collapse of Anak Krakatau

Abstract: The lateral collapse of Anak Krakatau volcano, Indonesia, in December 2018 highlighted the potentially devastating impacts of volcanic edifice instability. Nonetheless, the trigger for the Anak Krakatau collapse remains obscure. The volcano had been erupting for the previous six months, and although failure was followed by intense explosive activity, it is the period immediately prior to collapse that is potentially key in providing identifiable, pre-collapse warning signals. Here, we integrate physical, micro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Plagioclase compositions, indeed, are particularly sensitive to changes in temperature, H 2 O pressure (pH 2 O), and H 2 O content [Cutler et al 2022]. As shown in Figure 6, the first clear compositional difference through time is in the higher anorthite content (An 61-68 ) of the November plagioclase compared with that erupted in September (An 53-66 ); the more calcic plagioclases suggest relatively higher pH 2 O and temperatures [Couch 2003;Cutler et al 2022], as well as increasing melt maficity as observed also by Ubide et al [2023]. Other differences observed are lower K 2 O and Na 2 O and higher Al 2 O 3 contents in plagioclases from November compared with September.…”
Section: Discussionmentioning
confidence: 99%
“…Plagioclase compositions, indeed, are particularly sensitive to changes in temperature, H 2 O pressure (pH 2 O), and H 2 O content [Cutler et al 2022]. As shown in Figure 6, the first clear compositional difference through time is in the higher anorthite content (An 61-68 ) of the November plagioclase compared with that erupted in September (An 53-66 ); the more calcic plagioclases suggest relatively higher pH 2 O and temperatures [Couch 2003;Cutler et al 2022], as well as increasing melt maficity as observed also by Ubide et al [2023]. Other differences observed are lower K 2 O and Na 2 O and higher Al 2 O 3 contents in plagioclases from November compared with September.…”
Section: Discussionmentioning
confidence: 99%
“…In the intervening period, important new research on giant landslides has been published from many parts of the Atlantic Ocean including Cape Verde (Martínez-Moreno et al 2018;Barrett et al 2020;Cornu et al 2021), the Azores (Hildenbrand et al 2018;Marques et al 2020Marques et al , 2021, the Canary Islands (Coello-Bravo et al 2020), and the Lesser Antilles (Solaro et al 2020) as well as the Bismarck Archipelago in the Pacific Ocean (Watt et al 2019). Moreover, the collapse of Anak Krakatau on 22 December 2018 stimulated much research (Williams et al 2019;Grilli et al 2019Grilli et al , 2021Hunt et al 2021;Cutler et al 2022) and it is anticipated that the collapse of Hunga Tonga-Hunga Haʻapai on 15 January 2022 will provide the impetus for many new studies. Consequently, this feels like an auspicious time to update the global giant landslides on volcanic islands database.…”
Section: Southern Pacific Oceanmentioning
confidence: 99%
“…We also actively induce the destabilisation as we pull on the paper representing the sliding plane, which is different to the natural process. At Anak Krakatau, gravitational instability mixed with the structural architecture of the cone and caldera causing the gradual sliding are considered to be the most likely explanation (Hunt et al, 2021;Cutler et al, 2022). This also prevents any quantitative assessments inferring the stresses, pressures, or strains acting on the faults using the scaled models as the underlying processes are not the same, however, the resulting structural architecture is likely comparable.…”
Section: Modelling Limitationsmentioning
confidence: 99%